2014
DOI: 10.5812/hepatmon.18556
|View full text |Cite
|
Sign up to set email alerts
|

Serum Thrombopoietin Levels and Its Relationship WithThrombocytopenia in Patients With Cirrhosis

Abstract: Background:Patients with cirrhosis usually have thrombocytopenia in discrete levels. The mechanism of thrombocytopenia is thought as splenic sequestration and destruction of platelets, impaired bone marrow generation and diminished hepatic thrombopoietin synthesis.Objectives:The aim of this study was to evaluate serum thrombopoietin levels and its relationship with thrombocytopenia at patients with cirrhosis.Patients and Methods:Ninety–two cirrhotic patients and 45 healthy controls without history or findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 24 publications
4
22
0
3
Order By: Relevance
“…Our results showed that prothrombin time, and TSB were significantly higher among Child's B, whereas the value of the albumin was significantly lower. These findings were in agreement with other literatures [19]. Liver is the only organ for synthesis of albumin and thus liver cirrhosis impairs albumin synthesis.…”
Section: Figuresupporting
confidence: 83%
“…Our results showed that prothrombin time, and TSB were significantly higher among Child's B, whereas the value of the albumin was significantly lower. These findings were in agreement with other literatures [19]. Liver is the only organ for synthesis of albumin and thus liver cirrhosis impairs albumin synthesis.…”
Section: Figuresupporting
confidence: 83%
“…Como mencionado previamente, níveis de trombopoetina e contagem de plaquetas são altamente correlacionados com dano da função hepática e severidade da fibrose hepática em pacientes infectados com VHC cronicamente 25 Por mais que níveis séricos baixos de TPO estejam associados com cirrose hepática, em alguns estudos foram encontrados níveis normais e até mesmo aumentados de TPO sérico em pacientes cirróticos 38 .…”
Section: Resultados E Discussõesunclassified
“…Concluíram, também, que infecção por HCV é altamente associada com trombocitopenia a qual está fortemente associada à dano hepatocelular e fibrose hepática. No entanto, trombocitopenia é uma anormalidade laboratorial que não pode ser considerada como um sintoma específico para diagnóstico 24 , mesmo sendo a anormalidade hematopoiética mais comum em pacientes com cirrose hepática crônica 38 .…”
Section: Diagnósticounclassified
“…Patients with cirrhosis usually exhibit thrombocytopenia in discrete levels. The mechanism of thrombocytopenia is hypothesized to involve the splenic sequestration and destruction of platelets, impaired bone marrow generation and diminished hepatic thrombopoietin synthesis (23).…”
Section: Discussionmentioning
confidence: 99%